Exosome-based delivery of RNAi leads to breast cancer inhibition - Silva, Renata (2022)
Breast cancer is currently the most prevalent cancer in the world. It has been reported that hyperactivation and dysregulation of key pathways, such as PI3K/AKT/mTOR (PAM), contributes to the cell's tumorigenesis and resistance to existent therapies. Herein, we sought to uncover the potential of PAM downregulation in a panel of different breast cancer cell lines with different phenotypes, through PIK3CA silencing. This oncogene was targeted with a pre-designed small interfering RNA (siRNA) transfected onto PIK3CA wild-type MDA-MB-231cells and PIK3CA mutated MDA-MB-453cells. The results suggest that the siRNA efficiently targeted PIK3CA, triggering an efficient gene silencing and a decrease on cellular viability, as well as migration capacity. Moreover, exosome-like nanovesicles were successfully isolated, characterized and incorporated into the cells and served as excellent siRNA nanocarriers, promoting an incremented and faster onset. Altogether, the data gathered shows that the combination of the validated siRNA with these nanocarriers could be a promising targeted drug delivery system for an alternative breast cancer therapy.